Adverse Drug Reactions Study of Antihypertensive Drugs in Primary Care Settings - Yeni Farida; Kharimah Faizathus Tsalatsatun (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
Hypertension is one of the high-prevalence diseases in primary care. Failure to achieve the target of blood pressure is affected by non-compliance due to the antihypertensive adverse reactions. This study aims to determine adverse drug reaction (ADR) of antihypertensive drugs in primary care settings. A cross sectional study was conducted in “Sibela” Primary Care in Surakarta on March 2019. Investigators interviewed patients directly and observed supporting data from medical records. Hypertension patients with antihypertensive drugs at least for a month were eligible in this study.  Then, the data were analyzed by the Liverpool algorithm that interpreted in 4 scales: unlikely, possible, probable, and definite.  A total 70 subject were dominated by female (80%). Monotherapy of antihypertensive drugs prescribed to patient in primary care were amlodipine (80%) and captopril (10%). Nine events of ADR were found in hypertension patient. None ADR were doubtful. Possible ADR of amlodipine was drowsiness (5.4%), whereas probable ADR were nausea (3.4%), diuresis (1.8%), and abdominal pain (1.8 %). Definite ADR of captopril was dry mouth (14.3%) and probable ADR was abdominal pain (14.3%). Further investigation regarding the drowsiness, ADR of amlodipine, was needed.